Learning to Live With HIV in the Rural Townships: A Photovoice Study of Men Who Have Sex With Men Living With HIV in Mpumalanga, South Africa. (May 2017) - Daniels, Joseph; Maleke, Kabelo; Lane, Tim; Struthers, Helen; McIntyre, James; Kegeles, Susan; Moore, Alison; Coates, Thomas
Abstract : N/A: There is limited understanding about the health and well‐being of men who have sex with men (MSM) with HIV infection living in rural African areas. We present the results of an adapted photovoice project with 35 MSM with HIV infection who live in townships in Mpumalanga, South Africa. The project was designed to explore the social factors that influenced HIV care. Twenty‐four photo essays were developed by participants in focus group discussions that were audio‐recorded and transcribed for analysis. Transcripts and photo essays were coded using a constant comparison approach combining researcher observation notes and reflection on participant‐identified themes. Participants identified (a) a shared experience of illness and coming to terms with having HIV infection and (b) family and taverns as necessary support systems. The findings suggested that family‐ and tavern‐based interventions might improve health outcomes for MSM newly diagnosed with HIV infection living in rural and semi‐rural African communities.